Acute Intermittent Porphyria in Childhood Presenting with Hypertensive Emergency and Posterior Reversible Encephalopathy Syndrome - Rishab Bharadwaj; Pallavi P Dagli; Aasheeta S Shah (Wolters Kluwer Medknow Publications, 2016)
Acute intermittent porphyria is an inherited metabolic disease due to deficiency of the enzyme porphobilinogen deaminase that can affect the autonomic, peripheral and central nervous system. We report an 8 year old female who had presented with hyponatremia, psychiatric manifestations, seizures, hypertension and Posterior Reversible Encephalopathy Syndrome (PRES) with a delayed diagnosis of Acute Intermittent Porphyria. As porphyria is thought to be very rare in pre-pubertal age, in view of the potentially fatal outcome of a severe attack, a high index of suspicion is essential.